Literary Philosophy and the Use of Uselessness - Jarvie, Scott A; Frattura, Addyson (Art/Research International, 2021)
We build this work from the memory of the time we stumbled into tulips at city hall. As guard sirens fled off into the night, we wondered, “Maybe we can borrow some.” We ripped handfuls from the ground and ran. “Don’t worry,” we said, “they are too busy to catch us stealing tulips.” Likewise, we get away with this useless project because others are busy doing useful work: exigent, coherent, important work. We support much of that busyness, and at the same time wonder what is lost with all that attention towards usefulness. What we offer here, through a hybrid of reflective, poetic, essayistic and scholarly forms, may be an attempted escape from the obligations of scholarship. It may be indulgent. It may tell the reader nothing, or only what the reader already knows. Yet it is oriented towards an enduring promise. This is the promise of a literary experience, understood as a kind of resonance, ineffable primarily, but nevertheless one that matters. Such a promise is found in the power and possibility of story, through poetic lines that must be broken and conceptual tethers left incommensurable. We enter this space of breaking and unfurling through an inquiry into use.The question of use and uselessness is one way of holding human contradictions in both hands. By this we mean that we make and leave space for literary and philosophical inquiries considered useless—in that they do not resolve anything—but nevertheless matterful. We suggest that readers meander these curated pages as they \ meander through an art exhibition or a museum. Within a literary exhibition one can wander through pages, spaces, and ideas. Pause. Dwell. Think. We curate a literary home beyond the demands of making something of use and we invite the reader to sit with us. As with an exhibition, possibility cannot be controlled for and so we exist in potentiality acknowledging both its positive and negative potential. Through our use, misuse, and abuse of literature and philosophy, we make ourselves a home in a possibility that can only be offered, not demanded. We manifest this literary home through fragments of philosophy evoked through a series of microfictions.As scholars, learners, teachers, and writers we are often asked to defend what our writing does. And it is implicitly suggested that knowledge creation is the result. What is the use of a work that cannot promise new knowledge? Literary knowledge may only be one gorgeous possible ordering. It is a practice which produces a kind of knowledge which is no knowledge, which is useless.  If we must answer what it is that our writing does we suppose that—if anything—it offers up fictions for philosophizing. We explore a home for this work in scholarly contexts which too often find it useless, which is to say we position uselessness as a concept of value for our work as scholars, writers, and teachers. In the end we name no new uses but fiction; we steal tulips.